First Eigenvalue of p-Laplacian Along The Normalized Ricci Flow on Bianchi Classes - Habibi Vosta Kolaei, Mohammad Javad; Azami, Shahroud (IndoMS, 2020)
Consider M as a 3-homogeneous manifold. In this paper, we are going to study the behavior of the first eigenvalue of p-Laplace operator in a case of Bianchi classes along the normalized Ricci flow also we will give some upper and lower bounds for a such eigenvalue.